2009
DOI: 10.1111/j.1574-6968.2009.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved culturability of SAR11 strains in dilution-to-extinction culturing from the East Sea, West Pacific Ocean

Abstract: Although the SAR11 clade of the Alphaproteobacteria represents the most abundant and ubiquitous bacterioplankton in the ocean, very few laboratories have successfully cultured SAR11 cells. All of the SAR11 strains isolated thus far have been retrieved from the Oregon coast and the Sargasso Sea. In this study, a modified dilution-to-extinction culturing with prolonged incubation at low temperature was applied in an effort to cultivate major bacterioplankton lineages in the East Sea, Western Pacific Ocean. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 23 publications
0
53
1
Order By: Relevance
“…4b). In the class Alpha-proteobacteria, most clones of the samples of 1,000 m and 10 m belonged to the pelagic bacterial groups of the SAR clade that have been ubiquitously and predominantly detected in the East Sea (Song et al, 2009). As described, the back trajectory analysis showed that the air masses at 1,000 m and 10 m were suspended over the Sea of Japan in the 3 days prior to sampling.…”
Section: Bacterial Populations Carried From Marine Regionsmentioning
confidence: 97%
“…4b). In the class Alpha-proteobacteria, most clones of the samples of 1,000 m and 10 m belonged to the pelagic bacterial groups of the SAR clade that have been ubiquitously and predominantly detected in the East Sea (Song et al, 2009). As described, the back trajectory analysis showed that the air masses at 1,000 m and 10 m were suspended over the Sea of Japan in the 3 days prior to sampling.…”
Section: Bacterial Populations Carried From Marine Regionsmentioning
confidence: 97%
“…In addition, the role of proteorhodopsin is starting to become clear, which may lead to a better understanding of the carbon flux in the ocean (78). This culture technique has now led to the culture of new members of this clade from different marine regions (75) as well as other previously uncultured isolates from both marine and freshwater environments (15,33,36,59,79).…”
Section: Approaches To Culturing the Missing Bacterial Diversitymentioning
confidence: 99%
“…(Eguchi et al, 1996) are known to be ubiquitous marine oligotrophic ultramicrobacteria, which are thought to demonstrate improved survival at low substrate concentrations. The SAR clade is composed of ubiquitous and unculturable marine bacteria detected in the Sea of Japan (Song et al, 2009) and in ocean areas such as the Pacific Ocean (Giovannoni and Stingl 2005). Members of Pelagibacter, including the SAR clade, occupy approximately 25%-50% of marine bacteria in ocean areas, indicating their ability to survive in extreme environments (Morris et al, 2002).…”
Section: Alphaproteobacteriamentioning
confidence: 99%